Anais do 14º Encontro Sul-Rio-Grandense de Pesquisadores em História da Educação - (:unkn) unknown (Universidade Federal do Pampa, 2008)
The South-Rio-Grandense Association of Researchers in History of Education - Asphe, created in 1995, with profitable contributions to the history of Brazilian education and Rio-Grandense. . Asphe and the History of Education magazine have been privileged spaces of socialization of researches, of dynamization of the historiographic production and of important debates in the field of historical research, built collectively with the participation of all associates and which confer a singular significance to the Association.
Keywords: Docência; Educação; Ensino; CNPQ::CIENCIAS SOCIAIS APLICADAS